Higher Efficiency of Turbine Qil Purification - E. V. Toropov; I. F. Pshenisnov; A. I. Pshenisnov; Ya. I. Pshenisnov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Analysis of turbine oil purification has made it possible to ascertain the reason of failures in the system of T-200-130 LMZ turbine-driven set at South Urals Hydroelectric Power Station. This reason is non-effective operation of a coarse filter and high wear of a bearing No.4. The filter has been modernized and the required normative oil purity in the system of bearing lubrication and turbine-driven set regulation has been obtained.It has been shown that sieve fabric of polyamide monofilaments ensures effective filtration of contaminated oil in the system of bearing lubrication and steam turbines.Particle-size analysis of turbine oil impurities in various points of oil supply system can be used for technical diagnostics of turbine-driven set bearings.